Setting the scene for a multi-map toolset supporting maritime spatial planning by mapping relative cumulative impacts on ecosystem service supply - Armoškaitė, Aurelija; Aigars, Juris; Andersone, Ingrīda; Bonnevie, Ida Maria; Hansen, Henning Sten; Strāķe, Solvita; Thenen, Miriam von; Schrøder, Lise (Frontiers in Marine Science, 2023)
The aim of this paper is to provide the foundations for the development of a spatial decision-support toolset that combines cumulative impacts and ecosystem service supply assessments to support what-if scenario analysis in a maritime spatial planning context. Specifically, a conceptual framework for a toolset has been designed in order to introduce a new approach for place-based assessments of change in relative ecosystem service supply in multiple services at a time due to changes in cumulative impacts. Central to the toolset are two pre-existing approaches for relative ecosystem service supply and cumulative impact assessments and tools that facilitate them. The tools take advantage of available data from various sources, including geodata and expert knowledge, and have already been proven to support maritime spatial planning in a real-world context. To test the new approach and demonstrate the outputs, an ecosystem service supply assessment was done manually using the two currently separate tools. The results of the test case ecosystem service supply assessment for the Gulf of Riga in the Baltic Sea are also presented in this paper and illustrate the assessment steps and data needs. Although presently the focus of the illustrative assessment is the Gulf of Riga, the toolset will be able to accommodate analysis of cumulative impacts and service supply of any location, leaving the scope of the assessment to be determined by the objectives of the assessment as well as data availability (i.e., geospatial data availability and extent of expert knowledge).